Optical and EPR study of Mn4+ ions in different crystal environments in Mn, Li co-doped MgO - L. Borkovska; K. Kozoriz; I. Vorona; O. Gudymenko; S. Ponomaryov; O. Melnichuk; V. Trachevskii; O. Chukova; L. Khomenkova (Optical Materials: X)
The influence of Li ion on the symmetry of Mn4+ center and its photoluminescence (PL) in MgO:0,01%Mn, 3 % Li ceramics is studied by the X-ray diffraction, electron paramagnetic resonance (EPR), PL and optical absorption methods. It is shown that Li co-doping stimulates conversion of Mn2+ on Mg site into Mn4+ and can decrease symmetry of Mn4+ in a case of their specific close arrangement in the crystal lattice. Two kinds of Mn4+ centers are identified in the EPR and PL spectra: cubic Mn4+ and tetragonal complex Mn4+-Li+. The parameters of corresponding EPR centers are estimated from the experimental spectra (gcub = 1.994, |A|cub = 70.9 × 104 cm−1; g1tetr = g2tetr = 1.994, g3tetr = 1.993, |A|tetr = 71 × 104 cm−1, |D|tetr = 220 × 104 cm−1). The PL lines observed in the low temperature PL spectra are assigned to the specific Mn4+ related centers using a complementary study of PL excitation spectra and temperature dependent PL spectra. The lines at 654 nm and 671 nm are ascribed to R-line of Mn4+ in a site of cubic symmetry and its phonon overtone, correspondingly, as well as the lines at 666 nm and 681 nm are attributed to R2 line of Mn4+ in site with tetragonal symmetry and to its phonon overtone, correspondingly. It is shown that in Mn doped MgO ceramics made without intentional Li co-doping, the cubic Mn4+ center can be present and contribute to the PL spectra.